Effect of Involvement Culture on Performance of Selected 5-Star Chain Affiliated-Hotels in Kenya - Rotich, Lucy; Kiprop, Caroline (elixirpublishers, 2017)
The paper sought to establish the effect of involvement culture on performance of selected 5-star Chain affiliated hotels in Kenya. The study employed descriptive research design. The study was undertaken in Nairobi Central Business District (CBD). The target population of this study comprised of employees and managers of four 5-star chain hotels. The researcher employed purposive sampling, stratified sampling and simple random sampling techniques. Questionnaires and interview schedule was used in data collection. Data was analyzed using descriptive statistics; frequencies and percentages while correlation analysis was used to assess the effect of involvement culture on performance. Involvement culture was found to have a positive but weak relationship with performance. The study indicated that, the organization should ensure that the employees have shared belief, values and expectation to ensure realization of performance. The researcher therefore recommends that, for organizations to achieve the desired performance all the employees in the organization should be involved to drive the performance agenda.
Keywords: Involvement Culture; Performance; 5-star; Chain Affiliated Hotels